Land Access and Poverty among Agricultural Households in Nigeria - John Chiwuzulum Odozi; Ruth Uwaifo Oyelere (Institute of Labor Economics (IZA), 2024)
The issue of land inequality has garnered renewed interest in development literature due to its potential impact on the welfare of smallholder farmers. Poverty reduction is a crucial sustainable development goal, and a clearer understanding of the factors contributing to poverty is essential for effective, targeted policy initiatives in Nigeria. Investigating the potential relationship between land access and household poverty-related outcomes is highly relevant for both land and social welfare policy and is the focus of our paper. Using data from the four waves of the Nigeria General Household Panel Survey (GHS), we examine how the amount of land an agricultural household operates and the value of that land affect the probability of living in poverty. We employ both a fixed effects and a correlated random effects approach to explore our research question. Our results suggest a significant relationship between land access, as measured by land size, and poverty incidence. We also find evidence suggesting nonlinearities in the relationship between land access and poverty.
Keywords: Q15; Q12; D31; I32; I30; O1; 330; land access; land value; Nigeria; poverty; land size; inequality